COMPARATIVE STUDY OF HYPERELASTIC MODELS FOR THERMOPLASTIC ELASTOMERS IN SOFT ROBOTICS - Saduk , Melsiani R F; Hattu, Edwin P D; Wabang , Jhon A; Hore , Duran; Nasaruddin, Nasaruddin; Pangalinan, Antonius Pangalinan (Jurnal Rekayasa Mesin, 2025)
The accurate prediction of mechanical behavior in thermoplastic elastomers (TPEs) is essential for improving the performance of soft robotic grippers. This study presents a comparative evaluation of three hyperelastic models—Neo-Hookean, second-order Yeoh, and first-order Ogden—applied to NinjaFlex (TPU), Filaflex (TPE), and Pebax (PEBA). Finite Element Analysis (FEA) was conducted in ANSYS to assess total deformation, equivalent strain, and von Mises stress under internal pressures of 0.08–0.30 MPa. The Yeoh model captured the large-strain behavior in flexible materials, while the Ogden model provided balanced predictions across various stiffness levels. Neo-Hookean served as a computationally efficient baseline but showed limited accuracy under high strain. These findings provide a simulation-based framework for material–model selection in soft robotics and highlight the importance of model–material compatibility in design.